UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA MELALUI DISCOVERY LEARNING BERBANTUAN GEOGEBRA - Quratulaini, Istiklalia; Yuliyanti, Sri; Kurniawan, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to improve students' mathematical creative thinking skills through the implementation of the Discovery Learning model assisted by GeoGebra. This research was motivated by the low level of students' mathematical creative thinking skills, as indicated by the pre-cycle test results showing that only 1 out of 32 students (3.12%) achieved the minimum mastery criterion. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The subjects of the study were 32 students of class X.2 at SMAN 9 Mataram in the 2025/2026 academic year. Data were collected through tests, observations, interviews, and documentation. The learning process was carried out using the Discovery Learning model assisted by GeoGebra on the topic of Systems of Linear Equations in Two Variables (SLETV). The results showed a significant improvement in students' mathematical creative thinking skills. Learning mastery increased from 3.12% in the pre-cycle stage to 87.50% in Cycle I, exceeding the predetermined success indicator of 75%. The improvement occurred because Discovery Learning encouraged students to actively discover concepts through investigation and problem-solving activities, while GeoGebra facilitated concept visualization and exploration of various solution strategies. Therefore, the Discovery Learning model assisted by GeoGebra can be considered an effective alternative for improving students' mathematical creative thinking skills.